Prices for Common Services at Quaternary vs Nonquaternary Hospitals - Yan, Brandon W; Pany, Maximilian J; Dafny, Leemore S; Chernew, Michael E (JAMA : the journal of the American Medical Association, 2023)
This study uses commercial claims data to assess whether quaternary hospitals charge higher prices for common, unspecialized services also offered by nonquaternary hospitals.